2010
DOI: 10.1016/j.str.2009.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Legionella pneumophila Ecto -Triphosphate Diphosphohydrolase, A Structural and Functional Homolog of the Eukaryotic NTPDases

Abstract: Many pathogenic bacteria have sophisticated mechanisms to interfere with the mammalian immune response. These include the disruption of host extracellular ATP levels that, in humans, is tightly regulated by the nucleoside triphosphate diphosphohydrolase family (NTPDases). NTPDases are found almost exclusively in eukaryotes, the notable exception being their presence in some pathogenic prokaryotes. To address the function of bacterial NTPDases, we describe the structures of an NTPDase from the pathogen Legionel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
1
44
1
Order By: Relevance
“…Homology modeling of the NTPDase3 sequence revealed a high degree of structural fold similarity with a bacterial exopolyphosphatase (PDB 1T6C) that further refined structural predictions for members of the E-NTPDase family [145,193,194]. These similarities have now been substantiated by the determination of the crystal structures of the extracellular domain (ECD) of rat NTPDase2 [195] and the soluble NTPDase of the pathogenic bacterium L. pneumophila (LpNTPDase1), which is secreted into the replicated vacuole [196] (Table 3). Both enzymes share a sequence identity of approximately 20 %, and they both contain the five canonical ACR regions.…”
Section: Protein Structurementioning
confidence: 76%
“…Homology modeling of the NTPDase3 sequence revealed a high degree of structural fold similarity with a bacterial exopolyphosphatase (PDB 1T6C) that further refined structural predictions for members of the E-NTPDase family [145,193,194]. These similarities have now been substantiated by the determination of the crystal structures of the extracellular domain (ECD) of rat NTPDase2 [195] and the soluble NTPDase of the pathogenic bacterium L. pneumophila (LpNTPDase1), which is secreted into the replicated vacuole [196] (Table 3). Both enzymes share a sequence identity of approximately 20 %, and they both contain the five canonical ACR regions.…”
Section: Protein Structurementioning
confidence: 76%
“…Recently, functional homologues of CD39 have been identified in a number of microbial human pathogens (14), such as Legionella pneumophila (15)(16)(17), and proteins belonging to the CD73 family of ecto-5Ј-nucleotidase have been identified in Staphylococcus aureus, Bacillus anthracis, and Streptococcus sanguinis (18 -21). Inactivation of these bacterial ectonucleotidases impairs virulence but not viability, suggesting that their selective inhibition might be a new therapeutic strategy.…”
mentioning
confidence: 99%
“…14,24 Those three residues form an octahedral coordinated geometry for Ca 2+ ion in conjunction with the β-and γ-phosphate groups of nucleotides. 20 Therefore, we suggested that X residue in DXG motif may participate in the selectivity of the nucleotide which mediated divalent metal ion indirectly. Further structural analyses are needed to determine whether the position X in the DXG motif plays a critical role in the substrate recognition.…”
Section: Apyrasementioning
confidence: 93%
“…X-ray structural analyses revealed that ACR1 and ACR4 in rat apyrase (RnNTPDase2) and Legionella pneumophila apyrase (Lp1NTPDase) are involved in binding the β-and γ-phosphates of ATP. 20,21 In RnNTPDase2, divalent metal ion is thought to function as a catalyst by polarizing one of the P-O bonds of the terminal phosphate. 21 The importance of correct coordination of the cofactor is underpinned by the fact that mutation of residues involved in divalent metal ion binding (i.e., D45 in ACR1, D201 in ACR4, and W436 in ACR5) can result in loss of activity 13,14,22,23 or alteration of substrate and/or cofactor specificity and affinity.…”
Section: Apyrasementioning
confidence: 99%